Evaluating the advantages of a novel decentralised scheduling approach in the Industry 4.0 and Cloud Manufacturing era. Issue 13 (2019) - Vespoli, Silvestro; Grassi, Andrea; Guizzi, Guido; Santillo, Liberatina Carmela
Abstract: In the last year, the growing globalisation process has led to a radical change in the production concepts for which it is desirable to create value pursuing the customer need, pointing to provide more personalised product and services. At the same time, the rapid development of the Information Technologies (IT) enabled the creation of new manufacturing paradigm in which every machine is interconnected to each other: the Industry 4.0 and the Cloud Manufacturing. In this regard, this paper introduces a novel decentralised scheduling approach, starting to explore the available possibilities from these manufacturing paradigms. To this extent, a low-level shop floor controller of a Flow-Shop CONWIP production line with a predefined well-defined decision-making quote is introduced. This controller, composed of two newly logic elements to be placed in the production line upstream, is able to efficiently allocate the job within a predefined queue dynamically, following a proper dispatching rule. After the introduction of two different dispatching rule, we developed a hybrid simulation tool, validated on a reference model from the scientific literature, to evaluate the advantages of the introduced decentralised scheduling approach compared to a reference one. The results showed that the proposed low-level controller might lead to an important productivity increase without changing the manufacturing production line working parameter.